Declínio da aura, fotografia e cinema como espaço de jogo em Walter Benjamin - Bezerra, Francisco Rihelder Batista (2021)
This study aims to address the theme of aura decline and that of technical reproducibility in Walter Benjamin, especially in some of his essays in the 1930s, in which he deals with transformations in the mode of collective perception in the context of modernity. At first we analyzed the uses of the term aura by the German thinker until its conceptual formulation in the text Little history of photography (1931). Hence, we began to deal with the auratic phenomenon of the first photographs and the various historical-social factors that led to its decay, as well as a new qualitative dimension (in its scientific, physiognomic and political aspects) that photographic art acquires in the work of some important photographers. avant-garde profile. In the second chapter of our investigation and already in the context of the essay The work of art in the age of its technical reproducibility (1935), we note a resumption of several points in the 1931 text, however, with a significant change in the topic of the decline of the aura, this is now no longer restricted to the historical trajectory of photography, as it has been significantly extended to the entire history of art and its foundations. In fact, it overlaps that the aura and its experience concerns the way of being of the traditional work of art and that with the advent of modern reproduction techniques (photography and cinema), the aesthetic (contemplative) experience that concerns it is in a weakening process. In the third chapter, it is understood that with the auratic decline of the work of art, a new and fruitful possibility of artistic production, perception and reception is established in our time. Thus, cinema would be an innovative art for Benjamin and would mean a break in the history of art and traditional aesthetics. Having an affinity with the aesthetic category of the game (and not with that of the beautiful appearance), cinema would also be linked to the conception of a second technique, of a liberating and emancipatory character, as opposed to a first technique, with its own deleterious effects. of an increasingly technocratic world.